Prostanoid Receptors in the Human Vascular Wall - Xavier Norel (The Scientific World Journal)
The mechanisms involved in vascular homeostasis and disease are mostly dependent on the interactions between blood, vascular smooth muscle, and endothelial cells. There is an accumulation of evidence for the involvement of prostanoids, the arachidonic acid metabolites derived from the cyclooxygenase enzymatic pathway, in physiological and/or pathophysiological conditions. In humans, the prostanoids activate different receptors. The classical prostanoid receptors (DP, EP1–4, FP, IP, and TP) are localized at the cell plasma or nuclear membrane. In addition, CRTH2 and the nuclear PPAR receptors are two other targets for prostanoids, namely, prostacyclin (PGI2) or the natural derivatives of prostaglandin D2. While there is little information on the role of CRTH2, there are many reports on PPAR activation and the consecutive expression of genes involved in the human vascular system. The role of the classical prostanoid receptors stimulated by PGI2 and thromboxane in the control of the vascular tone has been largely documented, whereas the other receptor subtypes have been overlooked. There is now increasing evidence that suggests a role of PGE2 and the EP receptor subtypes in the control of the human vascular tone and remodeling of the vascular wall. These receptors are also present on leukocytes and platelets, and they are implicated in most of the inflammatory processes within the vascular wall. Consequently, the EP receptor subtypes or isoforms would provide a novel and specific cardiovascular therapeutic approach in the near future.